Sibling Spillover in Rural China: A Story of Sisters and Daughters - Cynthia Bansak; Xuan Jiang; Guanyi Yang (Institute of Labor Economics (IZA), 2020)
We find a strong positive sibling spillover effect in two-children households in rural China, as measured by an increase in the Chinese and Math test scores of elder siblings when their younger sibling starts school. We use the Chinese Law of Compulsory Education as an exogenous variation in the timing of school enrollment to control for the impact of simultaneous and unobserved out-of-sibship factors. The mechanism for the sibling spillover likely comes from an increase in studying interactions within the sibling pairs. The spillover is prompted by having a younger sister enter school and is the strongest when both children are daughters. However, the son-preference culture emphasized in certain regions negatively offsets the positive sister-led spillover.
Keywords: E24; C68; J30; 330; human capital; peer effect; sibling spillover; school cutoff; son preference; intrahousehold allocation; rural China